Interaksi Sosial Pemuda dan Lansia dalam Kegiatan Bakti Sosial: Perspektif Interaksionisme Simbolik di Panti Wreda Salib Putih - Putu Sherlina Junia Robin; Cindy Veronika Sihombing; Pierre Yehezkiel; Tabita Karen Debora; Maryati Kasmidi Hokoyoku; Natalia Alfiani Hapsari; Tunjung Wijanarka (Universitas Kristen Satya Wacana Salatiga, 2026)
This community service program is part of the Kuliah Praktik Lapangan or Institutional Practice Lecture (KPK) Satya Wacana Christian University Salatiga, which aims to increase social awareness among youth and provide emotional support for the elderly at the Salib Putih Elderly Care Home. This activity uses a participatory approach through fundraising, short worship services, sharing sessions, personal prayer, and the distribution of basic necessities. Symbolic interactionism theory analysis is used to examine how social meaning is formed through direct interactions between youth and elderly, particularly through symbols, language, expressions, and actions carried out during the activity. These interactions create warm emotional bonds, strengthen mutual understanding, and foster empathy. The results of the activity show increased social solidarity, the development of caring characters in youth, and the creation of psychological comfort for the elderly. Overall, this program confirms that KPK activities are able to build social meaning and strengthen solidarity through the process of symbolic interaction.